Tendencias del Tercer Sector a partir del análisis de las relaciones de interdependencia (2007)
ABSTRACT: This paper presents three different types of tendencies about third sector. This tendencies could be deduce in a network analysis based on interorganizational theories and resource dependence theory. This paper presents two study cases made at Medellin-Colombia. This show some categories that constitute characteristic tendencies of the sector.